Psychometric properties of the Jonsson-Abbott Scale: Rasch and confirmatory factor analyses - Forsström, David; Kottorp, Anders; Rozental, Alexander; Lindner, Philip; Jansson-Fröjmark, Markus; Carlbring, Per (Frontiers in Psychology, 2022)
Measuring and assessing the different aspects of gambling behavior and its consequences is crucial for planning prevention, treatment, and understanding the development of at-risk and problem gambling. Studies indicate that instruments measuring problem gambling produce different results based on the characteristics of the population assessed. To accurately measure at-risk and problem gambling behaviour, especially in a low-risk population, measures must cover a wider set of dimensions than negative consequences that are already manifest. The Jonsson-Abbott Scale (JAS) includes items that cover overconsumption, actions that reinforce gambling behaviour, and belief in gambling fallacies, based on a three-factor structure, and has previously shown good psychometric properties. However, there is a need to investigate how the instrument functions also in low-risk populations. The present study aims to do so using both confirmatory factor and Rasch analysis. The study included 1413 Swedish participants who endorsed at least one JAS item. The results replicated the three-factor solution reported previously and indicated that the instrument had good reliability. Also, the results showed that the three factors are independent and the overall score per factor needs to be analysed. In sum, the JAS appears to be suitable for use in low-risk populations to measure various aspects of gambling behaviour.